2019
DOI: 10.1094/mpmi-04-18-0096-r
|View full text |Cite
|
Sign up to set email alerts
|

Integration Host Factor Is Essential for Biofilm Formation, Extracellular Enzyme, Zeamine Production, and Virulence in Dickeya zeae

Abstract: Dickeya zeae is a globally important pathogenic bacterium that infects a number of crops, including rice, maize, potato, and banana. Bacterial foot rot of rice caused by D. zeae is one of the most important bacterial diseases of rice in China and some Southeast Asian countries. To investigate the functions of integration host factor (IHF) in D. zeae, we generated knockout mutants of ihfA and ihfB. Phenotypic assays showed that both the ΔihfA and ΔihfB strains had greatly reduced mobility, biofilm formation, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…The phenotypic traits affected by ihfA mutation in D. dadantii are by large similar to those reported in a recent study of Dickeya zeae strain lacking IHF [34]. However, there are also interesting differences.…”
Section: Correspondence Between Phenotypes and Relevant Genessupporting
confidence: 84%
See 1 more Smart Citation
“…The phenotypic traits affected by ihfA mutation in D. dadantii are by large similar to those reported in a recent study of Dickeya zeae strain lacking IHF [34]. However, there are also interesting differences.…”
Section: Correspondence Between Phenotypes and Relevant Genessupporting
confidence: 84%
“…In various Salmonella species IHF is shown to profoundly influence the expression of virulence genes, facilitate invasion associated with transition of bacterial cells to stationary phase [29] and promote biofilm formation [30]. IHF positively regulates the expression of virulence traits in human pathogens Vibrio cholerae [31] and Vibrio fluvialis [32] as well as in plant pathogens Erwinia amylovora [33] and Dickeya zeae [34]. In the soil bacterium Pseudomonas putida, IHF activates the genes involved in adaptation to the post-exponential phase with limited effect on genes involved in central metabolism [35].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, IHF may act upstream of another regulator that controls the expression of the identified genes. In the plant pathogen Dickeya zeae , IHF was suggested to positively regulate different virulence factors through binding to the promoter region of a diguanylate cyclase gene, increasing the production of the secondary messenger c-di-GMP (65). In F. perrara , we found that the transcriptional regulators BasR and DksA were substantially downregulated in the wt versus the ihfA* mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Banana starch along with these lactobacilli decreases pH, increases the production of lactic acid and short chain fatty acids from the intestinal microbiota (: a source of energy for the intestinal cells) and inhibits the population of others e.g. salmonella typhimurium SA2093 [90]. The plant fibers include polysaccharides, oligosaccharides and inulin which are fermented with intestinal microbiota influencing its composition and activity [91].…”
Section: Food Components Lead To Atherogenesis By the Induction Of Hymentioning
confidence: 99%